Design and Synthesis of Novel Fluorescent Phthalimide Based Silatranes: Ratiometric Estimation of Mg2+ Ion - Singh, Gurjaspreet; Mangat, Satinderpal Singh; Sharma, Hemant; Singh, Jandeep; Singh, Narinder (Asian Journal of Chemistry, 2017)
Organosilicon analogues of nitrogen-substituted phthalimide were synthesized and characterized by NMR (1H and 13C), ESI-MS and HRMS spectroscopic techniques. The recognition properties of fluorescent silatranes were studied and it was found that the structural variations play important role for metal recognition and one receptor has shown ratiometric estimation of Mg2+ over other tested metal ions.